The Imprecise Draftsmanship of the Lautenberg Amendment and the Resulting Problems for the Judiciary - Schneider, Melanie C. (Columbia Journal of Gender and Law, 2008)
In 1996, Congress passed the Domestic Violence Offender Gun Ban (“Lautenberg Amendment”), a controversial amendment to the Gun Control Act that makes it unlawful for individuals previously convicted of a misdemeanor domestic violence offense to possess a firearm. Legislative history shows that Congress intended to address state criminal laws that prosecute domestic violence as only a misdemeanor, which allows offenders to continue to possess firearms. Statutory interpretation is the only remaining avenue to challenge the Lautenberg Amendment and the courts’ improper interpretation of its meaning. In the rush of the legislative process, Congress hastily enacted Senator Lautenberg’s amendment, and this sheds light on the resulting problems for the judiciary, which is forced to interpret unclear statutory language. Congress has not corrected the Lautenberg Amendment, enacted over a decade ago. Further, numerous constitutional challenges to the Lautenberg Amendment have already failed.